2015
DOI: 10.1039/c5ra13161h
|View full text |Cite
|
Sign up to set email alerts
|

Covalent conjugation of carbon dots with Rhodamine B and assessment of their photophysical properties

Abstract: Applying the Förster formalism we studied the potential of urethane-like linkage at the surface of CDs to form donor–acceptor FRET pair in CD–Rhodamine conjugates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…As shown in Figure 6a, the absorption spectrum of RBITC features a typical band at 555 nm characteristic to the π-π* electronic transition in the xanthene ring [61]. Similar shifts of the absorbance peak were reported previously in other studies of Rhodamine conjugated to silver NPs or carbon dots (CD) [62,63]. Diac et al indicated the conversion of the isothiocyanate moiety in RBITC molecule to the thiourea upon the reaction with the terminal primary amine in the CD-PEG [58].…”
Section: Fluorescent Labelling Of Pt Nfssupporting
confidence: 86%
“…As shown in Figure 6a, the absorption spectrum of RBITC features a typical band at 555 nm characteristic to the π-π* electronic transition in the xanthene ring [61]. Similar shifts of the absorbance peak were reported previously in other studies of Rhodamine conjugated to silver NPs or carbon dots (CD) [62,63]. Diac et al indicated the conversion of the isothiocyanate moiety in RBITC molecule to the thiourea upon the reaction with the terminal primary amine in the CD-PEG [58].…”
Section: Fluorescent Labelling Of Pt Nfssupporting
confidence: 86%
“…FRET occurs without the appearance of a photon due to long range dipole-dipole interactions between CDs and quencher. The distance between the CDs and quencher was in the range of 10 Å-100 Å [19,[22][23][24]. The energy transfer efficiency (E) is calculated by following eq.…”
Section: Fret Mechanism Of Cdsmentioning
confidence: 99%
“…From that the CDs-quencher distance (r) and Förster distance (R 0 ) between the CDs and the quencher can be estimated by eq. 4-6: [22,23]…”
Section: Fret Mechanism Of Cdsmentioning
confidence: 99%
“…(3) The distance between the carbon dots and the quencher is 1–10 nm. [ 184–186 ] Soni et al. [ 136 ] used palm shell waste as biomass carbon source to synthesize N,S‐CQDs which could be applied to the detection of nitrophenol.…”
Section: Application Of Biomass Carbon Dots In Sensingmentioning
confidence: 99%